International law in antiquity / David J. Bederman. - Bederman, David J. (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2001)
This study of the origins of international law combines techniques of intellectual history and historiography to investigate the earliest developments of the law of nations. The book examines the sources, processes and doctrines of international legal obligation in antiquity to re-evaluate the critical attributes of international law. David J. Bederman focuses on three essential areas in which law influenced ancient state relations - diplomacy, treaty-making and warfare - in a detailed analysis of international relations in the Near East (2800-700 BCE), the Greek city-states (500-338 BCE) and Rome (358-168 BCE). Containing topical literature and archaeological evidence, this 2001 study does not merely catalogue instances of recognition by ancient states of these seminal features of international law: it accounts for recurrent patterns of thinking and practice. This comprehensive analysis of international law and state relations in ancient times provides a fascinating study for lawyers and academics, ancient historians and classicists alike.